Calcium increase in the mammillary bodies with aging - Patipath Suwannahoy (2018)
To elucidate compositional changes of the mammillary body with aging, the authors investigated age-related changes of elements, relationships among their elements, and gender differences in the mammillary bodies by direct chemical analysis. After ordinary dissection at Nara Medical University was finished, the mammillary bodies were resected from the cerebra of the subjects. The subjects consisted of 19 men and 25 women, ranging in age from 70 to 101 years (average age=83.8±7.2 years). After ashing of the mammillary bodies with nitric acid and perchloric acid, element contents were determined by inductively coupled plasma-atomic emission spectrometry. It was found that the Ca content increased slightly and significantly in the mammillary bodies with aging, but the P, S, Mg, Zn, Fe, and Na contents did not change significantly with aging. Regarding the relationships among elements, significant correlations were found among the contents of Ca, P, S, and Mg in the mammillary bodies, with one exception between P and Mg contents. With regard to the seven element contents, no significant gender differences were found in the mammillary bodies. © 2009 Humana Press Inc.